Ensuring the invariance of the pattern recognition system of the marine vessel systems in the process of fishing - Железняк, Александр Александрович; Каторин, Юрий Федорович; Сметюх, Надежда Павловна; Доровской, Владимир Алексеевич; Черный, Сергей Григорьевич (Eastern-European Journal of Enterprise Technologies, 2015)
Analysis of the existing algorithms for processing and transmitting video information for decision-making in information systems has shown that the existing algorithms do not consider the objective identification moments on the fishing fleet vessels. The problems of the impossibility of visualization of real images, clear separation of the object and the background, spatial arrangement of the points in the automated segmentation of digital images are displayed through the dependence by the features of adjacent frames in feature description methods. This necessitated the development of more detailed algorithms for the digital video data analysis, devoid of these shortcomings. This method involves the extraction of the contours of the object, which allowed to obtain a set of features and served as a basis for its analysis and recognition. Using the module of the normalized scalar product enabled to effectively solve the basic recognition problems - transfer, rotation and zooming of the object image. The assessment methods of digital video information were investigated. The main result of this study was the development of a tool for an integrated objective quality assessment of the data transmitted. The feature of the developed tool is that it is integrated into the Scanmar model that allows to simulate the multimedia processing and transmission networks with the assessment of quality losses in real time. The experiments, conducted using the developed tool, to assess the quality of video encoded by existing compression algorithms have shown that H.264 codec, which showed a higher video quality level than in similar compression by MPEG-4 and MJPEG codecs appears the most effective.